1996
DOI: 10.1042/bj3130597
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a cytosolic neutral chitobiase activity involved in oligomannoside degradation: a study with Madin-Darby bovine kidney (MDBK) cells

Abstract: Neutral oligomannosides possessing one GlcNAc (OS-Gn1) and two GlcNAc (Os-Gn2) at the reducing end have been reported to be released during the N-glycosylation process in various biological models. To investigate which enzyme is responsible for OS-Gn1 formation, we used the Madin-Darby bovine kidney (MDBK) cell line which exhibits neither lysosomal chitobiase nor endoglucosaminidase activities. However, these cells produced OS-Gn1 and we showed that a neutral chitobiase is responsible for the transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
(20 reference statements)
1
27
0
2
Order By: Relevance
“…Endoplasmic reticulum to cytosol transport of oligomannosides possessing two GlcNAc residues at the reducing end (OSGn 2 ) is known to be specific for nonglucosylated species (19,20). Moreover, it is now well established that OSGn 2 are converted to OSGn 1 species by a cytosolic chitobiase (21). Thus the finding of glucosylated OSGn 1 in MI8 -5 cells indicates that the deglycosylation process of glycoproteins occurred in the cytosol prior to their degradation.…”
Section: Discussionmentioning
confidence: 85%
“…Endoplasmic reticulum to cytosol transport of oligomannosides possessing two GlcNAc residues at the reducing end (OSGn 2 ) is known to be specific for nonglucosylated species (19,20). Moreover, it is now well established that OSGn 2 are converted to OSGn 1 species by a cytosolic chitobiase (21). Thus the finding of glucosylated OSGn 1 in MI8 -5 cells indicates that the deglycosylation process of glycoproteins occurred in the cytosol prior to their degradation.…”
Section: Discussionmentioning
confidence: 85%
“…8), the interaction of free OS with the lysosomal transporter bears similarities to the interactions between free OS and cytosolic glycosidases. Accordingly, the cytosolic chitobiase (15) by definition interacts with the reducing di-N-acetylchitobiose moiety of free OS, but more surprisingly, the cytosolic mannosidase has been found to act only on free OS bearing a single GlcNAc residue at their reducing termini (20). Therefore, these two enzymes and the cytosol-to-lysosome free OS transporter interact with free OS in a manner that involves surveillance of the reducing terminus of the oligosaccharide.…”
Section: The Lysosomal Free Os Transporter Displays a Unique Specificmentioning
confidence: 99%
“…In fact, neutral free OS are subject to sequential processing (15)(16)(17) by a previously characterized cytosolic endo-H-like activity (18) or chitobiase (15) and cytosolic mannosidase (19 -21) to yield a free OS containing five residues of mannose and a single reducing N-acetylglucosamine residue. It has now been demonstrated that this free OS is transferred to lysosomes in order to be degraded (17).…”
mentioning
confidence: 99%
“…The remaining free oligosaccharides (fOS) bear two GlcNAc residues at their reducing ends (called fOSGN2). They are subsequently trimmed by the ␤-endo-N-acetylglucosaminidase (ENGase), resulting in the formation of oligosaccharides possessing a single GlcNAc residue at their reducing ends (called fOSGN) (5). fOSGN may be also released directly from glycoproteins and glycopeptides by the direct action of ENGase (6).…”
mentioning
confidence: 99%
“…Misfolded glycoproteins originating in the lumen of the ER move to the cytosol to be degraded (4). An N-glycanase (PNGase) cleaves the N-linked glycans (5), which are reduced to Man 9 GlcNAc by an ENGase (6). Man 9 GlcNAc is then trimmed down to Man 5 GlcNAc by Man2c1 (7) prior to transfer into the lysosome (8).…”
mentioning
confidence: 99%